Exercise algebra.manipulation.exponential.equation

Description
solve exponential equation algebraically

Derivation

4^(2*x-3) == 2*sqrt 2
algebra.manipulation.exponents.factor-as-power
(2^2)^(2*x-3) == 2*sqrt 2
algebra.manipulation.exponents.write-as-power
(2^2)^(2*x-3) == 2*2^(1/2)
algebra.manipulation.exponents.mul-exponents
2^(2*(2*x-3)) == 2*2^(1/2)
algebra.manipulation.exponents.simple-add-exponents
2^(2*(2*x-3)) == 2^(3/2)
algebra.manipulation.exponents.equation.same-base
2*(2*x-3) == 3/2
algebra.equations.linear.distr-times
4*x-6 == 3/2
algebra.equations.coverup.onevar.minus-left
4*x == 15/2
algebra.equations.coverup.times
x == 15/8